Masalah Sosial Ekonomi Bencana Alam Erupsi Gunung Semeru di Kabupaten Lumajang Sebagai Sumber Belajar IPS - Tri Suci Ulamatullah; Sarmini; Nasution (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
Indonesia is the purpose of this study was to determine the socio-economic problems of the natural disaster of the Mount Semeru eruption in Lumajang Regency as a source of social studies learning. This research method is by using a qualitative case study approach. The data collection was carried out using interviews and participant observation and documentation to obtain data in the form of numbers. The subject of this research is the community affected by the eruption of Mount Semeru in Supiturang Village, Curah Kobokan, Lumajang Regency. This research will focus on socio-economic problems that emerged after the eruption of Mount Semeru natural disaster. Data analysis used is data collection, data reduction, data presentation, and drawing conclusions. The results of this study state that the socio-economic problems of the community after the natural disaster of the Mount Semeru eruption are (1) Loss of livelihood causes unemployment (2) Loss of property causes poverty. From these various socio-economic problems, the government made many efforts to overcome problems such as establishing temporary and permanent housing, receiving social assistance from various groups, providing social assistance from the government.